STUDI TENTANG IMPLEMENTASI DAN PEMAHAMAN NILAI-NILAI ADAT DALAM RAYO RUMAH GODANG PADA REMAJA DI KENEGERIAN SENTAJO KABUPATEN KUANTAN SINGINGI - ', Gustilianto; ', Zahirman; ', Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: In accordance with customary provisions required all public or adolescent from each tribe to go in or come to the house Godang, and follow all the stages that exist in Rayo home Godang, but especially young couple (teenagers) each tribal began to decline to assemble or bersilahturami Godang home or home for the feast kotonya Godang home or on the 2nd day of Eid Eid. Based on the above issue the writer take the title "Study on the implementation and understanding of traditional values in the home Rayo Godang in adolescents in Kenegerian Sentajo Regency Kuantan Singingi". Problem formulation in this research is how the implementation of the Rayo home Godang in adolescents and understanding of traditional values in the home Rayo Godang in adolescents in Kenegerian Sentajo Singingi Kuantan District. The purpose of this study is to investigate the implementation of the Rayo home Godang in adolescents and understanding of traditional values in the home Rayo Godang in adolescents in Kenegerian Sentajo Singingi Kuantan District. The population is 270 people and the sample amounted to 52 people. Instrument of data collection that the questionnaire consisted of 9 questions and 19 statements and interviews. Then the data was analyzed by qualitative descriptive through percentage. From the calculation of the percentage of respondents in getting answers to implementation as much as 35.1% unfavorable and understanding of traditional values of less good as much as 49.7%, which is located on the rank 25,01-50.00% Thus the hypothesis that the implementation of the Rayo home Godang and understanding of traditional values in the home Rayo Godang in adolescents both in Kenegerian Sentajo Regency Kuantan Singingi rejected. Based on the research results, it can be concluded that the study on the implementation and understanding of traditional values in the home Rayo Godang in adolescents in Kenegerian Sentajo Regency Kuantan Singingi is Not Good.Keywords: Implementation, understanding, values, Indigenous Rayo Home Godang